Pregabalin inhibits proinflammatory cytokine release in patients with fibromyalgia syndrome - Pınar Ellergezen; Alev Alp; Sinan Çavun; Melih Çelebi; Aslı Ceren Macunluoğlu (Archives of Rheumatology, 2023)
Objectives: The main goal of the study was to investigate how pregabalin (PGB) affects proinflammatory cytokine release in patients with fibromyalgia syndrome (FMS). Patients and methods: This experimental research study was conducted with 85 female participants (mean age: 49.6±10.1 years; range, 30 to 73 years) between April 2020 and November 2020. Of the participants, 30 were FMS patients using PGB 150 mg/day for at least three months, 30 were FMS patients not using PGB, and 25 were healthy individuals. The detection of FMS was carried out according to the 2010 American College of Rheumatology diagnostic criteria. Levels of proinflammatory cytokines (interleukin [IL]-2, IL-6, IL-12, IL-17, interferon-gamma, and tumor necrosis factor-alpha) were measured by enzyme-linked immunosorbent assay. Results: Serum concentrations of proinflammatory cytokines were remarkably decreased in FMS patients using PGB (p<0.001) and were higher in patients with FMS not using PGB than in healthy subjects (p<0.001). The highest values of proinflammatory cytokines were found in the group of FMS patients not using PGB (p<0.001). Conclusion: These results indicate that PGB inhibits the release of proinflammatory cytokines, suggesting that it can be used as an anti-inflammatory agent in inflammatory cases.